22. EVALUATING CHANGES IN REGIONAL CEREBRAL OXYGEN SATURATION USING NEAR- INFRARED SPECTROSCOPY AND SEVERAL FACTORS RELATED TO REGIONAL CEREBRAL OXYGEN DESATURATION IN PATIENT UNDERGOING CARDIOVASCULAR SURGERY (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate changes in regional cerebral oxygen saturation at various time points of surgery and identify several factors related to regional cerebral oxygen desarturation in cardiovascular surgery patients.Materials and methods: Observational study including 66 patients undergoing cardiovascular surgery with cardiopulmonary bypass using near-infrared spectroscopy as monitoring for regional cerebral oxygen starturation. At different time points of surgery, regional cerebral oxygen starturation, age, history of diseases, hemoglobin concentration, PaO2, mean arterial blood pressure were measured.Results: The baseline regional cerebral oxygen starturation was 65.32 ± 5.35%. Regional cerebral oxgen saturation increased immediately after anesthesia, reached the lowest value during cardiopulmonary bypass time (58.88 ± 4.60%), then increased and gradually returned to baseline value at the end of surgery. Age greater than or equal to 65 years, history of diabetes, mean arterial blood pressure lower than 50 mmHg and hemoglobin concentration less than 7.5 g/dl during cardiopulmonary bypass are associated with regional cerebral oxygen desarturation.Conclusion: Regional cerebral oxygen saturation increased immediately after anesthesia, reached the lowest value during cardiopulmonary bypass time. Several factors related to regional cerebral oxygen desarturation include age greater than or equal to 65 years, history of diabetes, mean arterial blood pressure lower than 50 mmHg and hemoglobin concentration less than 7.5 g/dl during cardiopulmonary bypass.
Keywords: Regional cerebral oxygen saturation; cardiovascular surgery; near infrared spectroscopy; cardiopulmonary bypass